2008
DOI: 10.1007/s00192-008-0735-3
|View full text |Cite
|
Sign up to set email alerts
|

Female sexual dysfunction: are urogynecologists ready for it?

Abstract: The aim of this study was to assess the practice of members of the British Society of Urogynaecology (BSUG) with respect to female sexual dysfunction (FSD) and compare it to members of the American Urogynecologic Society (AUGS). A web-based anonymous electronic questionnaire was sent to all (n = 150) BSUG members. Frequencies of responses and chi-square test for association with demographics were calculated. One hundred questionnaires were returned of which 95 were sufficiently filled. Fifty percent regularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 17 publications
5
27
1
2
Order By: Relevance
“…Our study further substantiates the importance of asking women about sexual problems when they present with urinary incontinence as it is a very common symptom, but unless asked, women will not divulge voluntarily this information [11]. Our study also dispels the belief traditionally held in relation to coital incontinence and found that urodynamic diagnosis is not linked to underlying sexual problems, orgasm or penetration incontinence.…”
Section: Discussionsupporting
confidence: 82%
“…Our study further substantiates the importance of asking women about sexual problems when they present with urinary incontinence as it is a very common symptom, but unless asked, women will not divulge voluntarily this information [11]. Our study also dispels the belief traditionally held in relation to coital incontinence and found that urodynamic diagnosis is not linked to underlying sexual problems, orgasm or penetration incontinence.…”
Section: Discussionsupporting
confidence: 82%
“…A number of previous surveys of similar national and international professional groups have been published, with response rates between 21% and 67%. 48,[96][97][98] None of these studies employed incentives to take part, and indeed none used reminder letters or e-mails. 95,99 Clearly the level of interest or excitement generated by the topic in potential respondents is of importance in encouraging responses.…”
Section: Clinicians' Viewsmentioning
confidence: 99%
“…Lack of time, ignorance of therapeutic options to treat sexual dysfunctions and the belief that sexuality is not an important issue among these women due to their advanced mean age, are the reasons referred to by professionals in order to justify why they do not systematically ask about sexual life when taking the urogynecological history. 12,13 The sexual lives of the women attended to in clinical practice in urogynecology can be grouped into a first group with pelvic Table 1 Major studies examining the activity and sexual function in women with pelvic floor disease.…”
Section: Resultsmentioning
confidence: 99%